Climate anomalies and international migration: A disaggregated analysis for West Africa - Fernanda Martinez Flores; Sveta Milusheva; Arndt R. Reichert (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
Migration is one of the channels West African populations can use to adjust to the negative impacts of climate change. Using novel geo-referenced and high-frequency data, this study investigates the extent to which soil moisture anomalies drive international migration decisions within the region and toward Europe. The findings show that drier soil conditions decrease (rather than increase) the probability to migrate. A standard deviation decrease in soil moisture leads to a 2 percentage point drop in the probability to migrate, equivalent to a 25 percent decrease in the number of migrants. This effect is concentrated during the crop-growing season, and likely driven by financial constraints. The effect is only seen for areas that are in the middle of the income distribution, with no impact on the poorest or richest areas of a country, suggesting that the former were constrained to start and the latter can address those financial constraints. – – Migration ist eine der Möglichkeiten, welche die westafrikanische Bevölkerung nutzen kann, um sich an die negativen Auswirkungen des Klimawandels anzupassen. Unter Verwendung neuartiger georeferenzierter und hochfrequenter Daten wird in dieser Studie untersucht, inwieweit Anomalien der Bodenfeuchte internationale Migrationsentscheidungen innerhalb der Region und in Richtung Europa beeinflussen. Die Ergebnisse zeigen, dass trockenere Bodenbedingungen die Migrationswahrscheinlichkeit verringern (anstatt zu erhöhen). Eine Abnahme der Standardabweichung der Bodenfeuchte resultiert in einem Rückgang der Migrationswahrscheinlichkeit um 2 Prozentpunkte, was einem Rückgang der Anzahl der Migranten um 25 Prozent entspricht. Dieser Effekt konzentriert sich auf die Anbausaison und wird wahrscheinlich durch finanzielle Einschränkungen verursacht. Der Effekt ist nur für Gebiete beobachtbar, die in der Mitte der Einkommensverteilung liegen, ohne Auswirkung auf die ärmsten oder reichsten Gebiete eines Landes, was darauf hindeutet, dass erstere zu Beginn eingeschränkt waren und letztere die finanziellen Beschränkungen ausgleichen können.
Keywords: F22; O13; O15; Q54; 330; West Africa; climate change; migration; agriculture